Marine algal flora of Graciosa Island, Azores - Neto, Ana I. (2020)
BACKGROUND: The macroalgal flora of Graciosa (central group of Azores archipelago) is poorly known, with only 116 species recorded so far (authors personal data). The published information reflects occasional collections from sporadic field visits to the Island. To overcome this, a thorough investigation under the Expedition “GRACIOSA/2004”, the Campaigns “PADEL/2006”, “MACROBIOLMOL/2014” and “PIMA-BALA/2017” involving sample collecting and presence data recording, was undertaken over an area of 19 km2 encompassing littoral and sublittoral levels down to about 40 m around the Island. This paper lists the taxonomic records and provides information on species ecology and occurrence around the Island improving the knowledge of the Azorean macroalgal flora at both local and regional scales. NEW INFORMATION: A total of 1692 specimens belonging to 250 taxa of macroalgae (and including 55 taxa identified only at the genus level) are registered, comprising 166 Rhodophyta, 36 Chlorophyta and 48 Ochrophyta (Phaeophyceae). From these, 195 are identified to the species level (126 Rhodophyta, 31 Chlorophyta and 38 Ochrophyta) and comprise 156 native, 20 of uncertain origin and 14 introductions to the Island. Predaea feldmannii subsp. azorica Gabriel is an Azorean endemic, whereas Codium elisabethiae O.C. Schmidt, Botryocladia macaronesica Afonso-Carrillo, Sobrino, Tittley & Neto, Phyllophora gelidioides P.Crouan & H.Crouan ex Karsakoff and Laurencia viridis Gil-Rodríguez & Haroun represent Macaronesian endemics. Seventy-nine species are newly recorded to the algal flora of the Island.